2021
DOI: 10.1016/j.celrep.2021.109084
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a VRC01-class germline targeting immunogen derived from anti-idiotypic antibodies

Abstract: SUMMARY An effective HIV-1 vaccine will likely need to elicit broadly neutralizing antibodies (bNAbs). Broad and potent VRC01-class bNAbs have been isolated from multiple infected individuals, suggesting that they could be reproducibly elicited by vaccination. Several HIV-1 envelope-derived germline-targeting immunogens have been designed to engage naive VRC01-class precursor B cells. However, they also present off-target epitopes that could hinder development of VRC01-class bNAbs. We characterize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Priming immunogens are engineered to interact with specific germline-encoded residues and lack CD4bs glycans that obstruct germline recognition 3 , 29 , 40 , 43 . VRC01-class priming immunogens include monomeric gp120 cores 25 , 40 , 44 , SOSIP-based trimers 3 , and anti-idiotypic antibodies that recognize target BCRs with VH1-2*02 gene segments 45 , 46 . Furthermore, selecting a particular strain of Env and a gp120- versus trimeric Env-based platform to engineer priming characteristics that have proven to impact germline BCR selection in vivo 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Priming immunogens are engineered to interact with specific germline-encoded residues and lack CD4bs glycans that obstruct germline recognition 3 , 29 , 40 , 43 . VRC01-class priming immunogens include monomeric gp120 cores 25 , 40 , 44 , SOSIP-based trimers 3 , and anti-idiotypic antibodies that recognize target BCRs with VH1-2*02 gene segments 45 , 46 . Furthermore, selecting a particular strain of Env and a gp120- versus trimeric Env-based platform to engineer priming characteristics that have proven to impact germline BCR selection in vivo 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, new anti-Id mAbs that bind with high-affinity multiple VRC01 precursors were developed. However, subsequent analysis revealed that these mAbs selectively recognize BCRs with either VRC01-class LCs featuring a 5-aa CDRL3 or with heavy chains derived from VH1-2 ∗ 02, but not BCRs possessing both characteristics [ 114 ]. The engagement and activation of B cells expressing VRC01 precursor-like BCRs were obtained through the engineering of a bispecific anti-idiotypic molecules derived from the anti-Id mAb iv9, that preferentially recognizes the VH1-2 ∗ 02 heavy chain, and the anti-Id mAb iv4 which tends to recognize LCs with 5-aa CDRL3 [ 114 ].…”
Section: Vaccinal Approaches Based On the Structure Of Anti-hiv Antib...mentioning
confidence: 99%
“…However, subsequent analysis revealed that these mAbs selectively recognize BCRs with either VRC01-class LCs featuring a 5-aa CDRL3 or with heavy chains derived from VH1-2 ∗ 02, but not BCRs possessing both characteristics [ 114 ]. The engagement and activation of B cells expressing VRC01 precursor-like BCRs were obtained through the engineering of a bispecific anti-idiotypic molecules derived from the anti-Id mAb iv9, that preferentially recognizes the VH1-2 ∗ 02 heavy chain, and the anti-Id mAb iv4 which tends to recognize LCs with 5-aa CDRL3 [ 114 ]. This bispecific anti-Id mAb iv4/iv9 activates iGL-VRC01 B cells in vitro , and in a murine adoptive transfer model, it displays superior engagement and expansion of VRC01 precursor B cells compared to iv4 or iv9 alone as Fab fragments [ 114 ].…”
Section: Vaccinal Approaches Based On the Structure Of Anti-hiv Antib...mentioning
confidence: 99%
“…Diffraction data from a single crystal were processed with HKL2000 32 . The Fab Lirilumab -KIR2DL3 complex structure was solved by molecular replacement using a Fab structure extracted from PDB 6XOC 33 and KIR2DL3 domains extracted from PDB 1B6U 30 with the PHASER 34 program. The structure was then partially rebuilt with the auto-build program within the PHENIX suite and completed manually using Coot followed by refinement using PHENIX.refine and Coot 35,36 .…”
Section: Structure Determination Of the Fab Lirilumab -Kir2dl3 Complexmentioning
confidence: 99%